2004
DOI: 10.1002/jnr.20350
|View full text |Cite
|
Sign up to set email alerts
|

Rasagiline: Neurodegeneration, neuroprotection, and mitochondrial permeability transition

Abstract: Mitochondria are involved directly in cell survival and death. The assumption has been made that drugs that protect mitochondrial viability and prevent apoptotic cascade-induced mitochondrial permeability transition pore (MPTp) opening will be cytoprotective. Rasagiline (N-propargyl-1R-aminoindan) is a novel, highly potent irreversible monoamine oxidase (MAO) B inhibitor anti-Parkinson drug. Unlike selegiline, it is not derived from amphetamine, and is not metabolized to neurotoxic L-methamphetamine derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 76 publications
3
104
0
Order By: Relevance
“…MAO inhibitors, at lower concentration, have shown antineuronal apoptosis and neuro-protection effects, independent of MAO inhibition (19)(20)(21)(22). Our study using higher concentrations of MAO A inhibitor, which inhibits MAO A catalytic activity, also produced effects on antineuronal apoptosis and neuro-protection.…”
Section: R1 or C-mycer Decreased Mao A Gene Expression But Increased mentioning
confidence: 47%
“…MAO inhibitors, at lower concentration, have shown antineuronal apoptosis and neuro-protection effects, independent of MAO inhibition (19)(20)(21)(22). Our study using higher concentrations of MAO A inhibitor, which inhibits MAO A catalytic activity, also produced effects on antineuronal apoptosis and neuro-protection.…”
Section: R1 or C-mycer Decreased Mao A Gene Expression But Increased mentioning
confidence: 47%
“…The non-amyloidogenic pathway, in which APP is sequentially cleaved by α-and γ-secretase, may prevent the production of Aβ (116,117). Several studies have reported that propargylamine-containing compounds, including ladostigil and M30, irreversible and selective MAO-B inhibitors, act as modulators of the proteolytic cleavage of APP via activation of the p42/44MAPK and PKC signaling pathways (61,(118)(119)(120). It was also demonstrated that M30 effectively inhibited Aβ accumulation and tau phosphorylation in APP/presenilin 1 mice, where it markedly downregulated the levels of phosphorylated cyclin-dependent kinase 5 and increased PKC and glycogen synthase kinase-3β phosphorylation (121).…”
Section: Activated Mao Contributes To the Formation Of Amyloid Plaquesmentioning
confidence: 99%
“…Previously, we demonstrated that the neuroprotective efficacies of the monoamine oxidase (MAO)-B inhibitor rasagiline are similar to those of the non-MAO inhibitor TVP1022, suggesting that cytoprotection is not due to MAO inhibition. 8,10 Furthermore, we recently reported that pretreat-ment of neonatal rat ventricular myocytes with TVP1022 or propargylamine attenuated doxorubicin and serum starvationinduced apoptosis. 9 More recently, we reported that TVP1022 increased phospho-protein kinase C and phospho-(Ser 9) glycogen synthase kinase-3␤ levels in H9c2 cardiomyoblasts and neonatal rat ventricular myocytes and prevented H 2 O 2 -induced damage in H9c2 by preserving the mitochondrial membrane potential and inhibiting cytochrome c release from the mitochondria.…”
Section: Clinical Perspective On P 473mentioning
confidence: 99%
“…[7][8][9] On the basis of the cytoprotective efficacies of propargylamines in neurodegenerative processes, 8,9 we tested the hypothesis that TVP1022 (the S-isomer of rasagiline; Azilect) will alleviate cardiac and renal dysfunction in experimental CHF in rats. Previously, we demonstrated that the neuroprotective efficacies of the monoamine oxidase (MAO)-B inhibitor rasagiline are similar to those of the non-MAO inhibitor TVP1022, suggesting that cytoprotection is not due to MAO inhibition.…”
Section: Clinical Perspective On P 473mentioning
confidence: 99%